Transnational Perspectives for Small and Medium-Sized Enterprises. How Interreg B supports SMEs. - (:unkn) unknown (My University, 2015)
Small and medium-sized enterprises (SMEs) form the backbone of the European economy. This category accounts for more than 98 per cent of all enterprises and makes up two thirds of all jobs in the private sector. If Europe wants to maintain its competitiveness and promotes intelligent, sustainable and inclusive growth in line with the objectives of the "Europe 2020" strategy, it is therefore particularly important to support SMEs. Transnational cooperation (better known under the name of Interreg B) can play an important role here. The examples presented in this brochure show how it is possible to successfully implement a large spectrum of measures with Interreg B which serve to promote and support SMEs. Until recently SMEs have less formally been involved as project partners in transnational cooperation, but were mainly target group and beneficiaries of project activities and their achievements. There is a greater focus on SMEs in the new programming period 2014-2020 and its alignment with the "Europe 2020" strategy. The purpose of this brochure, which was produced by the German Institute of Urban Affairs on behalf of the BBSR, is to show project stakeholders such as towns, cities and regions, but also SMEs themselves, the added value that this transnational cooperation can offer small and medium-sized enterprises and to give tips and advice for all those who are planning their own project activities.
Keywords: Wirtschaftsförderung; Wirtschaftspolitik; Unternehmenspolitik; Regionalentwicklung; Kooperation; Projektmanagement; INTERREG; Unternehmensförderung; Europäische Zusammenarbeit